Design of a real-time adaptable decoupled disturbance observer (Addob) on dual-stage controlled HDD systems - Lau, Chan Fan (2016)
In hard-disk drive (HDD) system, disturbance observer (DOB) is widely used to eliminate external disturbance which is introduced by audio vibration. However, this technology has not been developed in modem dual-stage controlled HDD system yet. Besides this, the performance of DOB is greatly relying on the design of its internal Q-filter. For simpler implementation, a pre-defined Q-fdter is used. It normally has fixed amplitude and bandwidth, based on the observation from actual HDD performance under worst case scenario. But, sometimes this may not optimize the performance of all the drives which may be operated in random environment, such as different temperature, humidity or air pressure. This project targets to design a real-time Adaptable Decoupled Disturbance OBserver (ADDOB) in a dual-stage controlled HDD system. The proposed technique may improve system’s ability in audio noise handling. The control loop ofboth actuators will install a DOB to tackle noises within certain frequency bands. Basically primary actuator will deal with lower frequency components while higher frequency components will be handled by secondary micro-actuator. Their Q-filter will be adjusted according to the output o f frequency detector. Phase lock loop (PLL) based algorithm is the main technique used here for frequency detection. The proposed system was developed and tested in a commercial HDD product. Test results had proven the effectiveness o f ADDOB. Any narrow band audio noise within 400Hz to 2.3 kHz was successfully detected and its impact on position error signal (PES) was eventually reduced by half.